2022
DOI: 10.1126/science.abq2787
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis treatment failure associated with evolution of antibiotic resilience

Abstract: The widespread use of antibiotics has placed bacterial pathogens under intense pressure to evolve new survival mechanisms. Genomic analysis of 51,229 Mycobacterium tuberculosis ( Mtb ) clinical isolates has identified an essential transcriptional regulator, Rv1830 , herein called resR for resilience regulator, as a frequent target of positive (adaptive) selection. resR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 60 publications
2
65
0
Order By: Relevance
“…Plates were incubated for 2-3 days at 37°C and images were captured with a 12-megapixel camera with a 120° FOV at 0, 6, 8, 13, 21, 25, 30, 36, 48, and 56 h after plating. Our previously devised colony tracing pipeline 44 was augmented with two deep learning models 45 that were trained to automate the identification of the grid lines of each plate and also to perform semantic segmentation of plate photos. The pipeline was applied as previously to track the expansion of individual colony areas over time and was repurposed to generate CFU counts displayed in Fig.…”
Section: Quantitative Imaging Of Colony Growthmentioning
confidence: 99%
“…Plates were incubated for 2-3 days at 37°C and images were captured with a 12-megapixel camera with a 120° FOV at 0, 6, 8, 13, 21, 25, 30, 36, 48, and 56 h after plating. Our previously devised colony tracing pipeline 44 was augmented with two deep learning models 45 that were trained to automate the identification of the grid lines of each plate and also to perform semantic segmentation of plate photos. The pipeline was applied as previously to track the expansion of individual colony areas over time and was repurposed to generate CFU counts displayed in Fig.…”
Section: Quantitative Imaging Of Colony Growthmentioning
confidence: 99%
“…Another recent study showed that the resR transcriptional regulator is a frequent target of positive selection for mutations and that strains with these mutations exhibit antibiotic “resilience,” which describes the potential for antibiotic tolerance and genetic resistance. The bacilli harboring these mutations exhibited more rapid post-antibiotic recovery than wild-type cells ( Liu et al., 2022 ). This new finding demonstrates that we must better understand the various strategies Mtb uses to recover from drug treatment beyond standard definitions of non-replication and dormancy so that we can design combination therapies that target these subpopulations.…”
Section: Looking Forward: the Future Of Tb Combination Therapy And Mo...mentioning
confidence: 99%
“…Rv1339, which has been implicated in modulating Mtb antibiotic susceptibility and is undergoing positive selection in TB patients globally was the only monogenic determinant associated with treatment failure (OR=5•34, CI=1•21-23•58, P=0•027), but not cavitary disease, suggesting disparate mechanisms may be accounting for these two distinct clinical outcomes associated with the L1.1.1.1 strains. 10,46,49 We performed Mantel-Haenszel analyses to ensure that the associations we identified with L1.1.1.1 and Rv1339 mutations are not explained by patient age or sex (S8 Table ).…”
Section: Mtb L1 Clade Is Associated With Poor Clinical Outcomes and I...mentioning
confidence: 99%
“…5,6 Recent studies have sought to use the wealth of Mtb whole genome sequencing data to find novel genetic associations with drug resistance, several of which have been experimentally shown to cause altered drug responses. [7][8][9][10] A few studies have sought to find bacterial genetic associations with more complex clinical outcomes like treatment failure, transmission, and dissemination. [10][11][12][13][14][15][16] Interpretation of genetic associations is complicated by Mtb's high degree of genetic linkage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation